Citizen science in South Africa: Rhetoric and reality. (July 2021) - Weingart, Peter; Meyer, Corlia
Citizen science, and public engagement with science, has become prominent in science policy programmes. Given the expectations attached to citizen science in academic and science policy discourses, it is worthwhile to look at where the actual work is done. The case of South Africa, the study focus, is interesting because the country follows similar programmes as many developed countries, but has a socioeconomically and educationally more unequal society. Thus, South Africa presented a test example of whether the institutional similarities of science or socioeconomic and educational differences prevail in shaping the reality of citizen science. Results from 56 projects showed that nearly all of them were limited to data collection in life science fields and were managed largely by one university and mainly communicated within the respective science communities. This led us to conclude that the ambitious rhetoric accompanying citizen science in science policy programmes is not matched by reality.